Missmatch Industri Dan SMK: Fenomena SMK Penyumbang Angka Pengangguran Tinggi - Dede Ridwan; Vina Dwiyanti (Journal Innovation In Education, 2024)
Vocational High Schools (SMK - Sekolah Menengah Kejuruan) have become the largest contributor to unemployment figures, contrary to their intended purpose of preparing graduates for the workforce. This issue is attributed to a mismatch between the needs of the industry and the education provided by vocational schools. The aim of this research is to identify steps that should be taken to reduce the industry-school mismatch. The method employed involves biometric analysis using Vos Viewer, with data sourced from Google Scholar, including scientific articles in journals and in English. The results and findings of this research indicate that the mismatch is caused by a lack of synchronization between industrial advancements and the curriculum in vocational schools, students' lack of preparedness for the job market, and various supporting skills. This study suggests further investigation into industry-school mismatches based on specific fields of expertise in each vocational school. Consequently, in the future, vocational schools should no longer be the leading contributor to unemployment but rather contribute to the workforce in various fields within industries, aligning with the demands of the respective industries.